Etos Kerja Islam Dan Ketahanan Usaha Kerajinan Tangan - Ahmad Ubaidillah; Misbahul Khoir (JES (Jurnal Ekonomi Syariah), 2019)
The objectives of research include; first, to describe what local Islamic working ethos are as the basis for the resilience of songkok, whip and slap handicraft businesses in Serah Panceng Gresik Village. Second, to describe the resilience of the songkok, whip and slap handicraft business in the village of Serah Panceng Gresik. This study is a qualitative-descriptive study with the aim of understanding the phenomena experienced by the subject of research including behavior, perception, motivation, and action holistically by utilizing various scientific methods. Data collection methods include; Observation, In-depth Interview or Focus Group Discussion, Documentation. Data analysis techniques include: processing and preparing data for analysis, reading the entire data, analyzing in more detail by coding data, considering detailed instructions that can help the coding process, giving descriptions that will be presented in the report, interpreting and interpreting data. The results showed that in Serah Village local Islamic working ethos were preserved by the community, such as alms giving, reading dziba', reading tahlil, attending haul akbar, and reading sholawat together every Friday. Although in the tradition it does not involve songkok, whip, and slap directly, there is a good impact to support the resilience of songkok, but not whip, and slap production. Religious rituals by praying together asking Allah to facilitate and carry out business in production songkok, whip, and slap are an expression of gratitude for what God gave to the people of Serah Village. All economic activity done by Serah community is meant to get God’s willing. Keywords: Islamic Working Ethos, Handicraft Businesses